2014
DOI: 10.1177/0001699314552807
|View full text |Cite
|
Sign up to set email alerts
|

From school to fitting work

Abstract: Although optimal labour market allocation of school leavers benefits individuals, employers and societies, a substantial part of European school leavers do not find a job that matches their field or level of education. This paper explores the extent to which horizontal and vertical education-to-job matches of European school leavers from secondary education is associated with the level of stratification, standardization, and the level of vocational orientation and institutional linkages of education systems. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 48 publications
(80 reference statements)
2
60
3
7
Order By: Relevance
“…Indeed, it is common practice among stratification scholars to only focus on men in the analyses (e.g. Levels et al 2014b). More surprising is the fact that the association between returns to education and our macro variable of corporatism is stronger for males.…”
Section: Education Systems and The Returns To Overeducationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is common practice among stratification scholars to only focus on men in the analyses (e.g. Levels et al 2014b). More surprising is the fact that the association between returns to education and our macro variable of corporatism is stronger for males.…”
Section: Education Systems and The Returns To Overeducationmentioning
confidence: 99%
“…Breen 2005; Bol and Van de Werfhorst 2013), we believe that progress can be made by studying academically and vocationally trained employees separately (e.g Levels et al 2014b),. and focusing on the way institutions may shelter these groups from positional competition.…”
mentioning
confidence: 99%
“…A study found a lower incidence of horizontal mismatch among vocationally-trained individuals(Levels, van der Velden and Di Stasio, 2014).…”
mentioning
confidence: 99%
“…Our analysis can thus enhance our understanding of labor market inequalities by formal educational attainment. Many studies show that external differentiation exacerbates the labor market disadvantage of less-educated workers (Andersen and van de Werfhorst 2010; Gesthuizen, Solga, and Künster 2011; Levels, van der Velden, and Di Stasio 2014; Solga 2002, 2008; van de Werfhorst 2011). Scholars attribute this to a positive effect of external differentiation on skills differentials between less- and intermediate-educated individuals (e.g., Andersen and van de Werfhorst 2010), but this explanation has not been tested empirically.…”
mentioning
confidence: 99%